APPLICATION OF GUIDED INQUIRY METHOD IN LEARNING BAHASA FOR S-1 NURSING STUDENTS - Moh. Zainudin; Eka Nurjanah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
For S1 nursing students at the University of Bina Sehat PPNI Mojokerto, this study intends to detail the planning, implementation, and evaluation of the application of the guided inquiry approach. The lecturer solely serves as a facilitator while using the guided inquiry technique, which offers possibilities for students to actively participate in learning activities. Materials for creating community service proposals, carrying out community service, and writing articles about community service are examples of how the guided inquiry technique is applied. This study used a qualitative research design, which generates descriptive information via interviews, observations of people's behavior, or written or spoken statements from participants. Observation, interviews, and documentation are all forms of data collecting. The researcher's data analysis is summarized as follows: (1) Data compression In this activity, data are chosen based on their level of relevance and their relationship to data groupings. Additionally, data are gathered into one unit and codes are created. (2) presenting data by assembling pertinent data, and (3) drawing inferences to understand the significance of the sporadic symptoms. The use of the guided inquiry technique in language acquisition can be divided into three categories based on the findings and discussion: planning, implementing, and evaluating the application of the guided inquiry method. The guided inquiry approach is inserted into the student learning experience section of the lecturer planning section. Students use the guided inquiry approach in the application part, starting with problem-solving, hypothesis-making, evidence-gathering, hypothesis-testing, and conclusion-drawing. Additionally, the researcher created an evaluation criterion to test students' proficiency using the guided inquiry method. When the guided inquiry approach is used, students get learning opportunities, particularly ones that help them develop their speaking and writing skills, which are two forms of productive language. The kids' capacity to carry out instruction at school and produce articles for community service serves as evidence of this.